2020
DOI: 10.1364/ol.395316
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of laser-focused intensity greater than 10 times through a re-entrant cone in the petawatt regime

Abstract: A versatile method to enhance the laser pulse intensity by one order of magnitude from 8 × 10 20 W / c m 2 using a single plastic micro-cone target is proposed in this Letter. We found an increase of the initial laser pulse intensity by more than 10 times for a micro-cone tip diameter of 5 µm upon performing two-dimensional particle-in-cell simulations. Numerical simulations of the spatio-temporal elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Moreover, to break through the damage limit of solid‐state optical elements, some other plasma elements have also been developed by many groups for reflecting, refracting, focusing, and diffracting extremely high intensity laser pulses. [ 210–213 ] Although most of the current plasma optics are theoretical studies and experimental results are far from predictions, in our opinion, plasma optics in the future still have big potentials for further increasing the peak power/intensity from a pure‐optical laser facility.…”
Section: Capability‐boosting Technologiesmentioning
confidence: 99%
“…Moreover, to break through the damage limit of solid‐state optical elements, some other plasma elements have also been developed by many groups for reflecting, refracting, focusing, and diffracting extremely high intensity laser pulses. [ 210–213 ] Although most of the current plasma optics are theoretical studies and experimental results are far from predictions, in our opinion, plasma optics in the future still have big potentials for further increasing the peak power/intensity from a pure‐optical laser facility.…”
Section: Capability‐boosting Technologiesmentioning
confidence: 99%
“…These results prove that additional studies regarding the optimization of the setups geometry are highly recommended before the experiments. As a first remark, we can say that the multiple beam interference and reflections which occur during the ultra-intense laser pulse propagation through a target with conical geometry has a major contribution to the laser intensity enhancement and this effect depends in particular on the predefined geometric features of the setup [29] and the input laser beam profile. Thus, a conceptual explanation for these increased intensity values obtained for the top-flat input beam profile may emerge from a higher-order superposition of the bright fringes with the cone neck center.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The main benefits of cone targets appear to be an increased confinement of the laser light inside the cone and a more effective generation of hot electrons from the inner cone walls. In fact, numerical simulations have shown that inside a conical target the internal reflections of the laser beam towards the cone apex leads to a smaller focusing spot which increases the laser intensity with orders of magnitude, and also the electron density increases due to surface electron induced-flow [77,78].…”
Section: Conical Targetsmentioning
confidence: 99%